Development of a Remote Steel Pipe Cutting Robot System - Shin, Hocheol; Bae, Yeonggeol; Jung, Seungho; Choi, Yourak; Kim, Changhoi (2018 15th International Conference on Ubiquitous Robots (UR), 2018)
This paper describes the design of a remote control robot system for hazardous environments such as a severe accident or the dismantling of a nuclear power plant. Occasionally, it is necessary for a robot to carry out the cutting work. We designed the hardware of a robot system and the software architecture. The system to be developed is composed of a master device, a slave robot, and a mobile platform, as well as a telescopic mast that moves the slave robot to the desired position. The integrating program has a system component control module, a virtual guide implementing module, and egocentric remote control algorithms. In addition, we developed a cutting tool for the robot system and carried out a cutting test of a 2 inch steel pipe with 5 mm thickness.